Assessment of Retailers Marketing Trends of Dairy Products in Khartoum, Sudan (Journal of Veterinary Medicine and Animal Production, 2022)
Supermarket retailers in Khartoum State were the target of the study, where intentionally chosen random samples of 135 shops during 2013 were studied through collecting data using a scientifically structured questionnaire. The objectives of the study were to analyze the role of the retailers in the dairy product marketing value chain; classify and describe retailers’ marketing efforts and elaborate the market power of retailers towards consumers and input suppliers. Data collected were analyzed using the SPSS statistical programme. The study showed the role and importance of the retail sector that it could be considered a promising enterprise specially when considering dairy products marketing, some recommendations were thus made to yet enhance this impact through adoption of extensive communication and promotional efforts and that manufactures should adopt joint promotional efforts with the retailers to boost product sales.
Keywords: RETALIERS; DAIRY PRODUCTS; COMMUNICATION; PROMOTION